(untitled) (Journal of Tropical Pharmacy and Chemistry, 2025)
Rational drug treatments to avoid adverse drug reactions in neonates are depend on physiologic immaturity and age-related changes in pharmacokinetic and pharmacodynamic factor. This condition lead neonates more prone to adverse drug reaction than adults.The aim of this study was to estimate the prevalence of adverse drug reactions that occured at Dr. Ramelan Navy Hospital’s NICU observed in November 26th 2007 to January 26th 2008. It was also to analyze kind of medication that caused adverse drug reactions.The study employed 94 patients (5 premature neonates and 89 term neonates) who were observed perspectively from November 26th 2007 to January 26th 2008. Demographic data, drug therapy, relevant medical histories, laboratory data were recorded in this study. The study result was assessed by literature study. The study result were analysed with Descriptive analysis. The most common adverse drug reaction occurred in this population was potential adverse drug reaction (99.5%). The most adverse drug reaction generated from this study was come from the use of ampicillin sulbactam (42.7%), gentamisin (31.4%), ceftriaxone (16.2 %), amikacin (7.6 %), aminofilin (1.1 %), ampicillin (0.5 %), and dexamethasone (0.5 %). The study showed that almost all of adverse drug reaction occurred in this study was potential adverse drug reaction (99.5%).